Cytotoxic and genotoxic characterization of titanium dioxide, gadolinium oxide, and poly(lactic-co-glycolic acid) nanoparticles in human fibroblasts - Das, Gautom Kumar (2014)
Engineered nanomaterials have become prevalent in our everyday life. While the popularity of using nanomaterials in consumer products continues to rise, increasing awareness of nanotoxicology has also fuelled efforts to accelerate our understanding of the ill effects that different nanomaterials can bring to biological systems. In this study, we investigated the potential cytotoxicity and genotoxicity of three nanoparticles: titanium dioxide (TiO2), terbium-doped gadolinium oxide (Tb-Gd2O3), and poly(lactic-co-glycolic acid) (PLGA). To evaluate nanoparticle-induced genotoxicity more realistically, a human skin fibroblast cell line (BJ) with less mutated genotype compared with cancer cell line was used. The nanoparticles were first characterized by size, morphology, and surface charge. Cytotoxicity effects of the nanoparticles were then evaluated by monitoring the proliferation of treated BJ cells. Genotoxic influence was ascertained by profiling DNA damage via detection of γH2AX expression. Our results suggested that both TiO2 and Tb-Gd2O3 nanoparticles induced cytotoxicity in a dose dependent way on BJ cells. These two nanomaterials also promoted genotoxicity via DNA damage. On the contrary, PLGA nanoparticles did not induce significant cytotoxic or genotoxic effects on BJ cells.